Evaluasi Kualitas Tanah Sawah di Kecamatan Denpasar Utara Berbasis Sistem Informasi Geografis - Boy Fernando Sagala; I Dewa Made Arthagama; I Wayan Narka (Fakultas Pertanian, Universitas Udayana, 2021)
This study aims to determine the quality of paddy soil, to determine the limiting factors of paddy soil quality, to provide land management direction in an effort to improve the quality of paddy fields and to make soil quality maps. This research was conducted in Nort Denpasar District from December 2020 to February 2021. Soil quality evaluation was carried out using field survey methods and laboratory analysis. Soil quality evaluation data analysis was carried out by matching and scoring based on limiting factors of 10 minimum data set (MDS) determinant of soil quality rating (SQR). The results showed that the soil quality in the study location was classified as moderate to good soil quality. Soils with moderate soil quality are found in SLH 3 and SLH 4 while soils with good soil quality are found in SLH 1 and SLH 2. The factor limiting soil quality in the study area is the low N and C-biomass. Based on the results of the study, the management directions at the research location can be determined, namely by adding organic matter, fertilizing urea, setting cropping patterns and applying intercropping.